Dual MOF fiber membrane for rapid degradation of chemical warfare agent simulants and preparation method and application thereof

The existing nanofiber membrane was solved by co-assemblying UIO-66-NH2 and MIL-101 (Cr) on the PAN fiber membrane mediated by PDA to form PAN/UIO-66-NH2/MIL-101 (Cr) composite nanofiber membranes In the technology, the poor removal effect of chemical warfare agents and the stability of MOF materials have achieved efficient removal of various chemical warfare agents and good mechanical properties.

CN116334841BActive Publication Date: 2025-02-25SHANDONG UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310307399.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-27
Publication Date
2025-02-25
Estimated Expiration
2043-03-27

AI Technical Summary

Technical Problem

The prior art has the risk of secondary desorption after adsorption when removing chemical warfare agents (CWAs), and there is a problem of crystallization powder in actual use and recycling of MOF materials, resulting in poor catalyst shedding and removal effects.

Method used

By co-assembly of UIO-66-NH2 and MIL-101 (Cr) on electrospun PAN fiber membranes under PDA mediation, PAN/UIO-66-NH2/MIL-101 (Cr) composite nanofiber membranes are formed. Enhance the adhesion and stability of MOF.

Benefits of technology

The composite nanofiber membrane showed enhanced synergistic enhancement of the detoxification effect of nerve agent simulator DMNP and erosive agent simulator CEES, and maintained good mechanical properties and acid-base resistance. It is suitable for the manufacture of personal protective equipment on the battlefield .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116334841B_ABST
    Figure CN116334841B_ABST
Patent Text Reader

Abstract

The present invention relates to a dual MOF fiber membrane for rapid degradation of chemical warfare agent simulants, a preparation method and an application thereof, wherein the chemical composition of the composite fiber membrane is PAN / UIO-66-NH2 / MIL-101(Cr). Electrospinning technology is combined with PDA chemistry, and UIO-66-NH2 and MIL-101(Cr) are in situ assembled on a PAN nanofiber membrane substrate through PDA mediation to form a PAN / UIO-66-NH2 / MIL-101(Cr) composite nanofiber membrane. The PAN / UIO-66-NH2 / MIL-101(Cr) composite fiber membrane DMNP and CEES of the present invention exhibit excellent catalytic and removal properties, and DMNP is completely hydrolyzed in a NEM buffer system in a very short time, while CEES is quickly and effectively captured through physical adsorption / chemical binding, thereby achieving rapid detoxification of two different chemical warfare agent simulants.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a composite nanofiber membrane with dual MOFs synergistically enhancing chemical warfare agent simulant removal performance, a preparation method and application thereof, and belongs to the field of catalytic chemistry. Background Art

[0002] Chemical warfare agents (CWAs) are among the most toxic man-made compounds to date, and are extremely harmful to the human respiratory system and skin. Natural toxic substances extracted from plants or animals have been widely used since the Middle Ages, but chemical warfare agents were first used on a large scale on the battlefield in the last century. Therefore, it is urgent to provide the military and the people with an effective protection measure against complex chemical warfare agents.

[0003] The earliest reported personal protective equipment (PPE) isolated the body from any contact with CWAs by using gas masks and impermeable clothing containing activated carbon. Although the effect is good, various thermal stress problems associated with impermeable clothing limit the long-term use of such protective equipment on the battlefield. At present, the ideal protective clothing mainly utilizes the adsorption and / or degradation (i.e., physical adsorption and / or chemical degradation) of CWAs. So far, the most effective materials for adsorbing CWAs are activated carbon and its derivatives, which are widely used by military forces around the world. Despite this, this material still has problems such as the possibility of secondary desorption of toxic substances in the pores of activated carbon after adsorption, causing casualties, and the low saturation of the adsorbent makes it difficult to effectively treat the contaminated protective equipment. Therefore, detoxification of CWAs by catalytic adsorbents is the most effective and promising research direction.

[0004] Metal-organic frameworks (MOFs) have highly tunable structures and functions, high porosity, large specific surface area, and abundant catalytic sites. Therefore, they have been regarded as a promising candidate material for CWAs adsorption and decontamination and have received tremendous research attention. In the past decade, Zr-based MOFs have been considered as highly promising materials for rapid degradation of nerve agents. UIO-66-NH2 is a representative Zr-MOF, which is assembled by coordination bonds between Zr6(μ3-O)4(μ3-OH)4 clusters and 2-aminoterephthalic acid. It shows good activity against real nerve agents and their simulants, but has low removal effect on blistering agents and their simulants. In addition, the internal pore size of UIO-66-NH2 is very small, making it difficult for many large-pore CWAs molecules to enter the interior of MOFs. MIL-101(Cr), with the molecular formula Cr3F(H2O)2O[(O2C)-C6H4-(CO2)]3nH2O (n value = ~25), is a kind of nanostructured ... MOF materials with higher crystallinity are considered to be excellent adsorbents that can effectively capture CWAs. The inventor of the present invention's previous patent document CN108310982A discloses a chemical warfare agent self-disinfecting metal-organic framework fiber filter membrane and a preparation method thereof. However, due to the tendency of MOF to crystallize into fine powder crystals, there are inevitable problems in the actual use and recovery of the catalyst. Therefore, a good solution is to combine MOF and fabric materials to synthesize MOF composite fiber membranes with certain mechanical properties and catalytic functions. For example: CN109603910A discloses a photothermal enhanced degradation of a nano-core-shell complex of a chemical warfare agent simulant and a preparation method and application of its composite fiber membrane. However, the binding ability of MOF and the fiber membrane is weak, and the problem of catalyst shedding is easy to occur during use. More importantly, the above patents can only achieve the removal of a single chemical warfare agent.

[0005] Therefore, developing novel methods to prepare MOF membrane materials that can effectively remove CWAs and have good stability remains a huge challenge. Summary of the invention

[0006] In order to solve the above problems, the present invention provides a composite nanofiber membrane with dual MOF synergistically enhanced degradation of CWAs and its preparation method and application. Here, the present invention proposes a simple method to achieve the co-assembly of UIO-66-NH2 and MIL-101(Cr) on the electrospun PAN fiber membrane under PDA mediation, and finally form a PAN / UIO-66-NH2 / MIL-101(Cr) composite nanofiber membrane.

[0007] The PDA coated on the PAN nanofibers in the present invention promotes the uniform deposition of MOFs crystals on the fibers, while increasing their adhesion, so that the MOFs particles can be firmly loaded on the surface of the nanofibers, thereby overcoming the problem of reduced activity of the nanofiber membrane due to aggregation or shedding. More importantly, the PAN / UIO-66-NH2 / MIL-101 (Cr) fiber membrane shows an enhanced synergistic enhanced detoxification effect on the nerve agent simulant DMNP and the erosive agent simulant CEES, which is attributed to the micro-mesoporous composite structure of UIO-66-NH2 and MIL-101 (Cr) combined with PDA. It is worth noting that due to the presence of the polydopamine layer, the MOF fiber membrane maintains good flexibility, bending resistance, acid and alkali resistance, mechanical strength and air permeability, which further highlights its viable material for manufacturing personal protective equipment on the actual battlefield, and provides a new solution for PPE used to deal with complex chemical warfare agents on the battlefield.

[0008] Terminology Note:

[0009] PDA: Polydopamine, a mussel-inspired polymer known for its high adhesion and abundant surface hydroxyl and catechol groups. It is also the main pigment of naturally occurring melanin.

[0010] PAN: polyacrylonitrile.

[0011] CWAs: Chemical warfare agents, a general term for a wide variety of toxic agents used on the battlefield.

[0012] PPE: Personal Protective Equipment.

[0013] MOFs: Metal Organic Frameworks.

[0014] UIO-66-NH2: An 8-coordinated Zr-based MOF assembled from Zr6(μ3-O)4(μ3-OH)4 and 2-aminoterephthalic acid through coordination bonds.

[0015] MIL-101(Cr): A Cr metal MOF, Cr3F(H2O)2O[(O2C)-C6H4-(CO2)]3nH2O (n value = ~25).

[0016] DMNP: a nerve agent simulant.

[0017] CEES: 2-Chloroethyl ethyl sulfide; a simulant of blister agents.

[0018] The technical solution of the present invention is as follows:

[0019] A composite nanofiber membrane for synergistically enhancing chemical warfare agent removal using dual MOFs, wherein the chemical composition of the composite nanofiber membrane is PAN / UIO-66-NH2 / MIL-101(Cr).

[0020] According to the present invention, preferably, the structure of the PAN / UIO-66-NH2 / MIL-101 (Cr) composite nanofiber membrane is as follows:

[0021] PDA was coated on PAN nanofibers, and MIL-101(Cr) nanoparticles and UIO-66-NH2 nanoparticles were loaded on the surface of nanofibers;

[0022] Further preferably, UIO-66-NH2 nanoparticles are also loaded on the surface of MIL-101(Cr) nanoparticles.

[0023] According to the present invention, preferably, the PAN nanofiber membrane is a fiber membrane interwoven with nanofibers having a diameter of 100-200 nm;

[0024] Preferably, UIO-66-NH2 is a nanoparticle with a diameter of 100-200 nm, and MIL-101(Cr) is a nanoparticle with a diameter of 400-600 nm.

[0025] According to the present invention, preferably, the MIL-101(Cr) is a MOF material formed by coordination between transition metal Cr clusters and terephthalic acid (BDC);

[0026] The UIO-66-NH2 is a MOF material formed by coordination between transition metal Zr clusters and aminoterephthalic acid (BDC-NH2).

[0027] According to the present invention, preferably, the mass ratio of PAN:MIL-101(Cr):UIO-66-NH2 in the PAN / UIO-66-NH2 / MIL-101(Cr) composite nanofiber membrane is (0.5-0.6):(0.1-0.2):(0.3-0.4), and most preferably 0.51:0.12:0.37.

[0028] According to the present invention, the method for preparing the above-mentioned dual MOF synergistically enhanced chemical warfare agent removal composite nanofiber membrane comprises the following steps:

[0029] During the uniform deposition of PDA on the electrospun PAN nanofiber membrane, MIL-101(Cr) and UIO-66-NH2 powders were in situ assembled to form a PAN / UIO-66-NH2 / MIL-101(Cr) composite nanofiber membrane with a MOF-on-MOF structure.

[0030] According to the present invention, preferably, the PAN nanofiber membrane is prepared by electrospinning;

[0031] Preferably, the electrospinning conditions are: a linear electrode is used as the spinning electrode, a cylindrical electrode is used as the receiving electrode, the electric field voltage is set to a positive pressure of 15 kV, a negative pressure of -1.5 kV, the spinning temperature is set to 25°C, the ambient humidity is set to 30% RH, the injection speed is set to 0.1 mm / min, aluminum foil is selected as the receiving device, and the distance between the spinning electrode and the aluminum foil is 15 cm.

[0032] According to the present invention, preferably, the process of depositing PDA on the PAN nanofiber membrane is:

[0033] The PAN fiber membrane was immersed in a Tris-HCl buffer solution, and dopamine hydrochloride self-polymerized and coated on the surface of the PAN fiber membrane;

[0034] Preferably, the pH of the Tris-HCl buffer solution is 7.5, and the concentration of dopamine hydrochloride is 2 mg / mL.

[0035] According to the present invention, preferably, the process of assembling MIL-101(Cr) and UIO-66-NH2 particles on the surface of PAN nanofibers is:

[0036] MIL-101(Cr) and UIO-66-NH2 were added to Tris-HCl buffer to obtain suspension A;

[0037] Add dopamine hydrochloride to A to obtain suspension B;

[0038] The PAN fiber membrane was immersed in the suspension B, and after being fully shaken on an oscillator, the product was washed to obtain a PAN / UIO-66-NH2 / MIL-101(Cr) composite nanofiber membrane.

[0039] According to the present invention, a method for preparing a composite nanofiber membrane for synergistically enhancing chemical warfare agent removal by dual MOFs, a preferred embodiment, comprises the following steps:

[0040] (1) Preparation of PAN fiber membrane

[0041] 1.0 g PAN was dissolved in 9.0 g DMF to form a uniform spinning solution, and then the spinning solution was injected into a 10 mL liquid reservoir, the linear electrode was used as the spinning electrode, the cylindrical electrode was used as the receiving electrode, the electric field voltage was set to 15 kV for positive pressure, -1.5 kV for negative pressure, the spinning temperature was set to 25 ° C, the ambient humidity was set to 30% RH, the injection speed was set to 0.1 mm / min, the fiber was collected on an aluminum foil 15 cm away from the spinning electrode, and dried at 60 ° C for 12 h to obtain an electrospun PAN fiber membrane;

[0042] (2) Preparation of MIL-101(Cr) nanopowder

[0043] 0.664 g of H2BDC (4 mmol) and 1.60 g of Cr(NO3)3.9H2O (4 mmol) were added to a solution of 0.8 mL of HF and 19.2 mL of deionized water and stirred for at least 30 min to allow the reactants to be fully mixed; the mixture was then transferred to a PTFE reactor and heated in an oven at 220°C for 8 h. The mixture was washed three times in DMF at 60°C to remove unreacted terephthalic acid to obtain MIL-101(Cr) crystals; it was then washed three times with anhydrous ethanol at 60°C to completely replace other solvents in the pores of MIL-101(Cr); finally, MIL-101(Cr) was vacuum dried at 150°C for 10 h to remove residual ethanol, water and other low-boiling impurities;

[0044] (3) Preparation of UIO-66-NH2 nanopowder

[0045] 0.08 g ZrCl4 (0.343 mmol) was added to a covered glass bottle containing 20 mL DMF and HCl (v:v=6:1); then ultrasonic treatment was performed for 5 min to completely dissolve ZrCl4; subsequently, 0.062 g (0.343 mmol) H2BDC-NH2 was added to the mixture and stirred continuously for 20 min; the glass bottle was heated in an oven at 120°C for 24 h; after the reaction was completed, the obtained product was collected by centrifugation and washed three times with DMF and ethanol; UIO-66-NH2 was activated by heating to 80°C in vacuum for 4 h before use;

[0046] (4) Preparation of PAN / UIO-66-NH2 / MIL-101(Cr) composite nanofiber membrane

[0047] 20 mg of pre-synthesized UIO-66-NH2 and 20 mg of pre-synthesized MIL-101(Cr) were added to 10 mL of Tris-HCl buffer (pH = 7.5) respectively, and ultrasonically stirred for 20 min to mix them evenly; 20 mg of dopamine (DA) was added to the suspension and stirred for 3 min; then, a 2x2 cm PAN electrospinning membrane was added to the suspension; the reaction was shaken on an oscillator for 4 h to obtain a PAN / UIO-66-NH2 / MIL-101(Cr) composite nanofiber membrane, and then the fiber membrane was ultrasonically treated in deionized water for 20 min to remove the assembled MOF and PDA particles; the fiber membrane was dried in a vacuum drying oven at 60°C for 4 h for activation before use.

[0048] According to the present invention, the application of the composite nanofiber membrane with dual MOF synergistically enhanced chemical warfare agent removal is used to degrade chemical warfare agent simulants; preferably, the chemical warfare agent simulants are at least one of nerve agent simulants and erosive agent simulants;

[0049] Preferably, the nerve agent simulant is DMNP.

[0050] Preferably, the erosive agent simulant is CEES.

[0051] The technical features and beneficial effects of the present invention are as follows:

[0052] 1. The present invention assembles two different types and sizes of MOF materials onto an electrospun PAN nanofiber membrane by utilizing the highly adhesive PDA produced during the DA polymerization process. The presence of the PDA layer brings about excellent adhesion and stability of the MOF on the fiber membrane, so that both MIL-101(Cr) and UIO-66-NH2 can be firmly loaded on the surface of the nanofiber membrane, overcoming the problems of easy shedding of traditional MOF fiber membranes due to MOF aggregation and reduced activity of the fiber membrane.

[0053] 2. The MOF-on-MOF structure of the PAN / UIO-66-NH2 / MIL-101(Cr) composite nanofiber membrane prepared by the present invention brings about an interesting synergistic effect between MIL-101(Cr) and UIO-66-NH2. The presence of the PDA layer enables UIO-66-NH2 to not only assemble on the PAN electrospinning membrane, but also firmly adhere to the exposed crystal surface of MIL-101(Cr). This MOF-on-MOF structure brings about a synergistic effect between the two MOFs, producing a better chemical warfare agent removal effect than the individual components, further proving the beneficial effects brought about by the rational design of the structure.

[0054] 3. The PAN / UIO-66-NH2 / MIL-101(Cr) composite nanofiber membrane prepared by the present invention can not only effectively and quickly hydrolyze DMNP, but also efficiently remove CEES, thus achieving a broad-spectrum application for a variety of chemical warfare agent simulants.

[0055] 4. The PAN / UIO-66-NH2 / MIL-101(Cr) composite nanofiber membrane prepared by the present invention has a good membrane morphology, maintains the mechanical properties of the PAN electrospinning membrane, has excellent chemical warfare agent removal effect, and also retains a certain mechanical strength, air permeability, flexibility, acid and alkali resistance, etc. It is a promising MOF membrane material for removing chemical warfare agents. BRIEF DESCRIPTION OF THE DRAWINGS

[0056] Figure 1 TEM images of UIO-66-NH2 powder (a) and MIL-101(Cr) powder (b) in Experimental Example 1; SEM images of PAN electrospun fiber membrane (c) and PAN / UIO-66-NH2 / MIL-101(Cr) composite fiber membrane (d)

[0057] Figure 2 SEM images of PAN / UIO-66-NH2 fiber membrane (a) and PAN / MIL-101(Cr) fiber membrane (b) in Experimental Example 1.

[0058] Figure 3This is the EDS distribution diagram of the PAN / UIO-66-NH2 / MIL-101(Cr) composite fiber membrane in Experimental Example 1.

[0059] Figure 4 These are the XRD of PAN fiber membrane, MIL-101(Cr), UIO-66-NH2, PAN / UIO-66-NH2 / MIL-101(Cr) composite fiber membrane, PAN / UIO-66-NH2 fiber membrane and PAN / MIL101(Cr) fiber membrane in Experimental Example 1.

[0060] Figure 5 FTIR of PAN fiber membrane, UIO-66-NH2, MIL-101(Cr), and PAN / UIO-66-NH2 / MIL-101(Cr) composite fiber membrane in Experimental Example 1.

[0061] Figure 6 This is the curve of DMNP conversion rate of different nanofiber membranes and MOF powders changing with time in Experimental Example 2.

[0062] Figure 7 These are the UV curve and pseudo-first-order kinetic curve of the hydrolysis of DMNP by the PAN / UIO-66-NH2 / MIL-101(Cr) composite fiber membrane in Experimental Example 2.

[0063] Figure 8 It is the PAN / UIO-66-NH2 / MIL-101(Cr) composite fiber membrane after complete hydrolysis of DMNP in Experiment 2. 31 PNMR.

[0064] Fig. 9 This is the removal rate-time curve of CEES by different nanofiber membranes and MOF crystals in Experimental Example 3.

[0065] Fig.10 The removal of CEES by PAN / UIO-66-NH2 / MIL-101(Cr) composite fiber membrane at different reaction times in Experiment 3 1 HNMR.

[0066] Fig.11 This is the GC-MS analysis of the PAN / UIO-66-NH2 / MIL-101(Cr) composite fiber membrane in Experimental Example 4 after CEES was removed.

[0067] Fig.12 This is the cyclic performance test of the PAN / UIO-66-NH2 / MIL-101(Cr) composite fiber membrane after removing DMNP and CEES in Experimental Example 5.

[0068] Fig.13The tensile stress curves (a) and air permeability (b) of PAN and PAN / UIO-66-NH2 / MIL-101(Cr) composite fiber membranes in Test Example 6. DETAILED DESCRIPTION

[0069] The present invention is further described below by means of specific examples, but is not limited thereto.

[0070] Example 1

[0071] A method for preparing a composite nanofiber membrane for synergistically enhancing chemical warfare agent removal by dual MOFs, wherein the chemical composition of the composite nanofiber membrane is PAN / UIO-66-NH2 / MIL-101 (Cr), comprising the following steps:

[0072] (1) Preparation of PAN fiber membrane

[0073] 1.0 g PAN was dissolved in 9.0 g DMF to form a uniform spinning solution, and then the spinning solution was injected into a 10 mL liquid reservoir, the linear electrode was used as the spinning electrode, the cylindrical electrode was used as the receiving electrode, the electric field voltage was set to 15 kV for positive pressure, -1.5 kV for negative pressure, the spinning temperature was set to 25 ° C, the ambient humidity was set to 30% RH, the injection speed was set to 0.1 mm / min, the fiber was collected on an aluminum foil 15 cm away from the spinning electrode, and dried at 60 ° C for 12 h to obtain an electrospun PAN fiber membrane;

[0074] (2) Preparation of UIO-66-NH2 powder

[0075] 0.08 g ZrCl4 (0.343 mmol) was added to a covered glass bottle containing 20 mL of a mixture of DMF and HCl (v:v=6:1). Ultrasonic treatment was performed for 5 min to completely dissolve the ZrCl4. Subsequently, 0.062 g (0.343 mmol) of H2BDC-NH2 was added to the mixture and stirred continuously for 20 min. The glass bottle was heated in an oven at 120 °C for 24 h. After the reaction was completed, the product was collected by centrifugation and washed three times with DMF and ethanol. UIO-66-NH2 was activated by heating to 80 °C under vacuum for 4 h before use;

[0076] (3) Preparation of MIL-101(Cr) powder

[0077] 0.664 g of H2BDC (4 mmol) and 1.60 g of Cr(NO3)3.9H2O (4 mmol) were added to a solution of 0.8 mL of HF and 19.2 mL of deionized water and stirred for at least 30 min to allow the reactants to be fully mixed. The mixture was then transferred to a PTFE hydrothermal reactor and heated in an oven at 220°C for 8 h. The mixture was washed three times in DMF at 60°C to remove unreacted terephthalic acid to obtain MIL-101(Cr) crystals. Subsequently, it was washed three times with anhydrous ethanol at 60°C to completely replace other solvents in the pores of MIL-101(Cr). Finally, MIL-101(Cr) was vacuum dried at 150°C for 10 h to remove residual ethanol, water and other low-boiling impurities;

[0078] (4) Preparation of PAN / UIO-66-NH2 / MIL-101(Cr) composite fiber membrane

[0079] 20 mg of pre-synthesized UIO-66-NH2 and 20 mg of pre-synthesized MIL-101(Cr) were added to 10 mL of Tris-HCl buffer (pH = 7.5) and ultrasonically stirred for 20 min to mix them evenly. 20 mg of dopamine hydrochloride (DA) was added to the suspension and stirred for 3 min. Subsequently, a 2x2 cm PAN electrospun membrane was added to the suspension. The reaction was shaken on an oscillator for 4 h to obtain a PAN / UIO-66-NH2 / MIL-101(Cr) composite nanofiber membrane, which was then ultrasonically treated in deionized water for 20 min to remove the unassembled MOF and PDA particles. The fiber membrane was dried in a vacuum oven at 60 ° C for 4 h before use for activation.

[0080] Example 2

[0081] The method for preparing the PAN / UIO-66-NH2 / MIL-101(Cr) composite nanofiber membrane is as described in Example 1, except that UIO-66-NH2 is not added in step (4).

[0082] Example 3

[0083] The method for preparing the PAN / UIO-66-NH2 / MIL-101(Cr) composite nanofiber membrane is the same as that described in Example 1, except that MIL-101(Cr) is not added in step (4).

[0084] Comparative Example 1: Preparation of PAN fiber membrane

[0085] 1.0g PAN was dissolved in 9.0g DMF to form a uniform spinning solution, and then the spinning solution was injected into a 10mL liquid reservoir. The linear electrode was used as the spinning electrode, and the cylindrical electrode was used as the receiving electrode. The electric field voltage was set to 15kV for positive pressure and -1.5kV for negative pressure. The spinning temperature was set to 25°C, the ambient humidity was set to 30% RH, and the injection speed was set to 0.1cm / h. The fibers were collected on an aluminum foil 15cm away from the spinning electrode and dried at 60°C for 12h to obtain an electrospun PAN fiber membrane.

[0086] Comparative Example 2, UIO-66-NH2 nanopowder

[0087] 0.08 g ZrCl4 (0.343 mmol) was added to a covered glass bottle containing 20 mL DMF and HCl (v:v=6:1). Then, it was sonicated for 5 min to completely dissolve the ZrCl4. Subsequently, 0.062 g (0.343 mmol) of H2BDC-NH2 was added to the mixture and stirred continuously for 20 min. The glass bottle was heated in an oven at 120°C for 24 h. After the reaction was completed, the obtained product was collected by centrifugation and washed three times with DMF and ethanol. UIO-66-NH2 was activated by heating to 80°C in vacuum for 4 h before use.

[0088] Comparative Example 3: MIL101 (Cr) nanopowder

[0089] 0.664 g of H2BDC (4 mmol) and 1.60 g of Cr(NO3)3.9H2O (4 mmol) were added to a solution of 0.8 mL of HF and 19.2 mL of deionized water and stirred for at least 30 min to allow the reactants to be fully mixed. The mixture was then transferred to a PTFE reactor and heated in an oven at 220°C for 8 h. The mixture was washed three times in DMF at 60°C to remove unreacted terephthalic acid to obtain MIL-101(Cr) crystals. Subsequently, it was washed three times with anhydrous ethanol at 60°C to completely replace other solvents in the pores of MIL-101(Cr). Finally, MIL-101(Cr) was vacuum dried at 150°C for 10 h to remove residual ethanol, water and other low-boiling impurities.

[0090] Comparative Example 4: Mechanically mixed PAN / UIO-66-NH2 and PAN / MIL-101(Cr) nanofiber membranes

[0091] The fiber membranes of Experimental Example 3 and Experimental Example 4 were cut into pieces and mechanically mixed according to the ratio of MOF loading.

[0092] Figure 1These are the TEM images of UIO-66-NH2 powder (a) in Example 1; MIL-101(Cr) powder (b); SEM images of PAN electrospun fiber membrane (c), and PAN / UIO-66-NH2 / MIL-101(Cr) composite fiber membrane (d).

[0093] Figure 2 It is the PAN / UIO-66-NH2 fiber membrane (a) in Example 2; and the PAN / MIL-101(Cr) fiber membrane (b) in Example 3.

[0094] Figure 3 This is the EDS distribution diagram of the PAN / UIO-66-NH2 / MIL-101(Cr) composite fiber membrane in Example 1.

[0095] Figure 4 These are the XRD of PAN fiber membrane, MIL-101(Cr), UIO-66-NH2, PAN / UIO-66-NH2 / MIL-101(Cr) composite fiber membrane in Example 1, PAN / UIO-66-NH2 fiber membrane in Example 2 and PAN / MIL101(Cr) fiber membrane in Example 3.

[0096] Figure 5 FTIR of PAN fiber membrane, UIO-66-NH2, MIL-101(Cr), and PAN / UIO-66-NH2 / MIL-101(Cr) composite fiber membrane in Example 1.

[0097] Figure 6 DMNP conversion rate of all samples in Examples 1-3 and Comparative Examples 1-3 changes with time.

[0098] Figure 7 These are the UV curve and pseudo-first-order kinetic curve of the hydrolysis of DMNP by the PAN / UIO-66-NH2 / MIL-101(Cr) composite fiber membrane in Example 1.

[0099] Figure 8 The PAN / UIO-66-NH2 / MIL-101(Cr) composite fiber membrane in Example 1 is completely hydrolyzed with DMNP. 31 PNMR.

[0100] Fig. 9 It is the removal rate-time curve of CEES for all samples in Examples 1-3.

[0101] Fig.10 The removal of CEES by the PAN / UIO-66-NH2 / MIL-101(Cr) composite fiber membrane at different reaction times in Example 1 is 1HNMR.

[0102] Fig.11 This is the GC-MS analysis of the PAN / UIO-66-NH2 / MIL-101(Cr) composite fiber membrane after CEES was removed in Example 1.

[0103] Fig.12 This is the cyclic performance test of the PAN / UIO-66-NH2 / MIL-101(Cr) composite fiber membrane after removing DMNP and CEES in Example 1.

[0104] Fig.13 The tensile stress curves (a) and air permeability (b) of PAN and PAN / UIO-66-NH2 / MIL-101(Cr) composite fiber membranes in Example 1.

[0105] Test Example 1

[0106] The UIO-66-NH2 powder in Test Example 1; TEM of MIL-101(Cr) powder; SEM of PAN electrospun fiber membrane, PAN / UIO-66-NH2 / MIL-101(Cr) composite fiber membrane, as shown in FIG. Figure 1 As shown. Among them, (a) UIO-66-NH2; (b) MIL-101(Cr); (c) PAN; (d) PAN / UIO-66-NH2 / MIL-101(Cr).

[0107] The SEM images of the PAN / UIO-66-NH2 fiber membrane in Test Example 2 and the PAN / MIL-101(Cr) fiber membrane in Test Example 3 are as follows: Figure 2 As shown. (a) PAN / UIO-66-NH2, (b) PAN / MIL-101(Cr).

[0108] The EDS distribution diagram of the PAN / UIO-66-NH2 / MIL-101(Cr) composite fiber membrane of Test Example 1 is as follows: Figure 3 shown.

[0109] The XRD patterns of the PAN fiber membrane, MIL-101(Cr), UIO-66-NH2, and PAN / UIO-66-NH2 / MIL-101(Cr) composite fiber membrane in Example 1, the PAN / UIO-66-NH2 fiber membrane in Example 2, and the PAN / MIL-101(Cr) fiber membrane in Example 3 were as follows: Figure 4 shown.

[0110] The FTIR of the PAN fiber membrane, MIL-101(Cr), UIO-66-NH2, PAN / UIO-66-NH2 / MIL-101(Cr) composite fiber membrane of Example 1, the PAN / UIO-66-NH2 fiber membrane of Example 2 and the PAN / MIL101(Cr) fiber membrane of Example 3 were tested. Figure 5 shown.

[0111] Depend on Figure 1 , 2 It can be seen that UIO-66-NH2 is a nanoparticle with a diameter of 100-200nm; MIL-101(Cr) is a nanoparticle with a diameter of about 500nm; PAN electrospun fiber membrane is a fiber membrane interwoven by nanofibers with a diameter of 100-200nm. UIO-66-NH2 and MIL-101(Cr) were successfully assembled on PAN nanofibers, and in PAN / UIO-66-NH2 / MIL-101(Cr), UIO-66-NH2 was not only assembled on PAN fibers, but also on the surface of MIL-101(Cr), which was also confirmed in the EDS distribution diagram ( Figure 3 ).

[0112] Depend on Figure 4 , 5 It can be seen that PAN / UIO-66-NH2 / MIL-101(Cr) simultaneously shows the special crystal peaks of UIO-66-NH2 and MIL-101(Cr) in XRD; and the Zr-O stretching vibration peaks of UIO-66-NH2 and the Cr-O stretching vibration peaks of MIL-101(Cr) (766, 585 cm -1 ), which confirms the successful assembly of MOF on PAN substrate.

[0113] Test Example 2

[0114] In order to evaluate the DMNP hydrolysis performance of PAN / UIO-66-NH2 / MIL-101(Cr), the following experiments were designed:

[0115] Place 18.1 mg of shredded PAN / UIO-66-NH2 / MIL-101(Cr) nanofiber membrane into 1 mL of 0.45 M NEM buffer solution and stir at 1100 rpm for 30 min. Subsequently, add 4 μL of DMNP to the above solution. At regular intervals, use a microinjector to transfer 25 μL of the reaction solution to a volumetric flask filled with 0.15 M NEM buffer solution and adjust the volume to 10 mL. Use UV-vis spectroscopy to measure the absorption peak intensity of the DMNP degradation product (p-nitrophenol) at 401 nm in the constant volume liquid as the basis for judging the hydrolysis process of DMNP, and calculate its pseudo-first-order rate constant k. The final degradation product of DMNP is also a process. 31 PNMR detection. When other conditions remain unchanged, the catalyst is replaced with the same molar equivalent of PAN, PAN / UIO-66-NH2, PAN / MIL101(Cr) fiber membrane, MIL-101, and UIO-66-NH2 powder.

[0116] The test results are as follows Figure 6 , 7 And as shown in Table 1.

[0117] Table 1

[0118]

[0119]

[0120] It can be seen that when UIO-66-NH2 powder is used as the catalyst, it exhibits the fastest degradation rate (t 1 / 2 , 0.38min), which is because the contact area between MOF powder and DMNP molecules is the largest, and the Lewis acid active sites are fully exposed. In contrast, MIL-101(Cr) and PAN hardly produce any degradation products and lack the Lewis acid sites required for hydrolysis of DMNP. It should be noted that due to the inevitable shielding effect of the inactive matrix, it is almost impossible for MOF fabric materials to achieve the degradation kinetics of the same amount of MOF powder. Nevertheless, PAN / UIO-66-NH2 / MIL-101(Cr) composite fiber membrane is also better than PAN / UIO-66-NH2(t 1 / 2 ,5.52min) showed a faster DMNP degradation rate (t 1 / 2,2.53min). This can be attributed to the synergistic effect of the MOF-on-MOF structure in the PAN / UIO-66-NH2 / MIL-101(Cr) composite fiber membrane. To verify this reason, PAN / UIO-66-NH2 and PAN / MIL-101(Cr) fiber membranes with the same MOF content were mechanically mixed as DMNP degradation catalysts, and the mixture showed a DMNP hydrolysis rate similar to that of PAN / UIO-66-NH2. This illustrates the rationality of the structural design of the PAN / UIO-66-NH2 / MIL-101(Cr) composite fiber membrane, and the synergistic effect of the two MOFs enables it to have faster DMNP degradation performance than the fiber membrane loaded with a single MOF. The solution after the PAN / UIO-66-NH2 / MIL-101(Cr) composite fiber membrane completely degraded DMNP was measured 31 P NMR, the results are as Figure 8 As shown, it can be seen that no other degradation products were generated.

[0121] *T 1 / 2 : The hydrolysis half-life of DMNP was calculated using the pseudo-first-order kinetic parameter k.

[0122] *TOF: (turnover frequencies) The turnover frequency of each SBU (Zr6 cluster) to DMNP molecules.

[0123] Test Example 3

[0124] In order to evaluate the CEES removal performance of PAN / UIO-66-NH2 / MIL-101(Cr) composite nanofibrous membrane, the following experiments were designed:

[0125] First, 60 mg of PAN / UIO-66-NH2 / MIL-101(Cr) nanofiber membrane was added to a 10 mL glass vial, which was then placed in a constant temperature and humidity chamber; the parameters were set at 25°C and 50% RH. After 0.5 h, the vial was sealed and 5 μL of CEES was injected into the vial through a microinjector. After 1.5 h, the entire system was extracted with CDCl3. After standing for a period of time, the supernatant was taken and used 1 H NMR was used to measure the CEES conversion. When other conditions remained unchanged, the catalyst was replaced with the same molar equivalent of PAN, PAN / UIO-66-NH2, PAN / MIL101(Cr) fiber membrane, MIL-101, and UIO-66-NH2 powder.

[0126] The experimental results are as follows Fig. 9 , 10As shown, it can be seen that due to the synergistic effect of UIO-66-NH2 and MIL-101(Cr), the PAN / UIO-NH2 / MIL-101(Cr) composite fiber membrane showed the fastest CEES removal rate (reaching 91% within 4 hours); the CEES removal rates of PAN / MIL-101(Cr) and PAN / UIO-66-NH2 fiber membranes were lower, 85% and 54% after 4 hours, respectively. In order to compare the removal rates of CEES by each component alone, the CEES removal rates of PAN, UIO-66-NH2 and MIL-101(Cr) were further tested. The results showed that the degradation rate of PAN / UIO-NH2 / MIL-101(Cr) composite fiber membrane was significantly higher, further confirming the synergistic effect of MIL-101(Cr) and UIO-66-NH2. MIL-101(Cr) provides a larger pore size to enhance the physical adsorption of CEES, while UIO-66-NH2 serves as the main component for CEES degradation. This physical adsorption / chemical degradation effect is the main source of the CEES removal ability of PAN / UIO-66-NH2 / MIL-101(Cr).

[0127] Test Example 4

[0128] In order to further evaluate the degradation products of PAN / UIO-66-NH2 / MIL-101(Cr) composite nanofibrous membrane after removing CEES, the following experiment was designed.

[0129] A certain amount of PAN / UIO-66-NH2 / MIL-101(Cr) composite fiber membrane was completely depleted of CEES and fully dissolved in a mixture of deuterated DMSO and HF. The solution was packaged and then measured by GC-MS.

[0130] GC-MS test results are as follows Fig.11 As shown, it can be seen that the presence of 2-hydroxyethyl sulfide (2-HEES, m / z values ​​106, 75 and 47), the hydrolysis product of 2-CEES, was monitored. This confirms that the removal of CEES by PAN / UIO-66-NH2 / MIL-101(Cr) composite fiber membrane includes physical adsorption and hydrolysis reaction.

[0131] Test Example 5

[0132] To evaluate the reusability of PAN / UIO-NH2 / MIL-101(Cr) composite fiber membrane, Fig.12 shown.

[0133] It can be seen that after PAN / UIO-NH2 / MIL-101(Cr) composite fiber membrane hydrolyzed DMNP and removed CEES for four consecutive times under the same conditions, the conversion rate decreased from 100% and 91% to 80% and 72%, respectively, attenuating by 20% and 19%, indicating that PAN / UIO-NH2 / MIL-101(Cr) composite fiber membrane has good cyclic reusability.

[0134] Test Example 6

[0135] The tensile properties, air permeability, acid and alkali resistance of PAN / UIO-66-NH2 / MIL-101(Cr) composite fiber membrane were tested. Fig.13 , as shown in Table 2, wherein: Table 2 is the adhesion and acid and alkali resistance test.

[0136] Table 2

[0137]

[0138] The results show that due to the presence of the PDA layer, the PAN / UIO-66-NH2 / MIL-101(Cr) composite fiber membrane maintains even better tensile properties than the original PAN substrate. The air permeability is slightly lower than that of the PAN fiber membrane, but it is still much better than common A4 paper and plastic film. At the same time, the PAN / UIO-66-NH2 / MIL-101(Cr) composite fiber membrane has good acid and alkali resistance, with only 2% and 3% mass loss after stirring in pH 2 HCl solution and pH 10 NaOH solution for 48 hours, respectively. These results show that the PAN / UIO-66-NH2 / MIL-101(Cr) composite fiber membrane is a MOF functional membrane material with good mechanical strength, acid and alkali resistance, and air permeability, which can adapt to a variety of different usage scenarios.

Claims

1. A composite nanofiber membrane for synergistically enhancing chemical warfare agent removal using dual MOFs, characterized in that: The chemical composition of the composite nanofiber membrane is PAN / UiO-66-NH2 / MIL-101(Cr); The structure of PAN / UiO-66-NH2 / MIL-101(Cr) composite nanofiber membrane is as follows: PDA is coated on PAN nanofibers, MIL-101(Cr) nanoparticles and UiO-66-NH2 nanoparticles are loaded on the surface of nanofibers, and UiO-66-NH2 nanoparticles are also loaded on the surface of MIL-101(Cr) nanoparticles. During the uniform deposition of PDA on the electrospun PAN nanofiber membrane, MIL-101(Cr) and UiO-66-NH2 powders were in situ assembled to form a PAN / UiO-66-NH2 / MIL-101(Cr) composite nanofiber membrane with a MOF-on-MOF structure. The process of assembling MIL-101(Cr) and UiO-66-NH2 particles on the surface of PAN nanofibers is as follows: MIL-101(Cr) and UiO-66-NH2 were added to Tris-HCl buffer to obtain suspension A; Dopamine hydrochloride was added to A to obtain suspension B; the PAN fiber membrane was immersed in the suspension B, and after being fully shaken on an oscillator, the product was washed to obtain a PAN / UiO-66-NH2 / MIL-101(Cr) composite nanofiber membrane.

2. The composite nanofiber membrane for synergistically enhancing chemical warfare agent removal according to claim 1, characterized in that: The PAN nanofiber membrane is a fiber membrane formed by interweaving nanofibers with a diameter of 100-200nm.

3. The composite nanofiber membrane for synergistically enhancing chemical warfare agent removal according to claim 1, characterized in that: UiO-66-NH2 is a nanoparticle with a diameter of 100-200 nm, and MIL-101(Cr) is a nanoparticle with a diameter of 400-600 nm.

4. The composite nanofiber membrane for synergistically enhancing chemical warfare agent removal according to claim 1, characterized in that: The mass ratio of PAN:MIL-101(Cr):UiO-66-NH2 in the PAN / UiO-66-NH2 / MIL-101(Cr) composite nanofiber membrane is (0.5-0.6):(0.1-0.2):(0.3-0.4).

5. The composite nanofiber membrane for synergistically enhancing chemical warfare agent removal according to claim 4, characterized in that: The mass ratio of PAN:MIL-101(Cr):UiO-66-NH2 in the PAN / UiO-66-NH2 / MIL-101(Cr) composite nanofiber membrane is 0.51:0.12:0.

37.

6. The method for preparing the composite nanofiber membrane for synergistically enhancing chemical warfare agent removal according to claim 1, comprising the following steps: During the uniform deposition of PDA on the electrospun PAN nanofiber membrane, MIL-101(Cr) and UiO-66-NH2 powders were in situ assembled to form a PAN / UiO-66-NH2 / MIL-101(Cr) composite nanofiber membrane with a MOF-on-MOF structure.

7. The method for preparing a composite nanofiber membrane for synergistically enhancing chemical warfare agent removal according to claim 6, characterized in that: The PAN nanofiber membrane is prepared by electrospinning; Electrospinning conditions: linear electrode was used as spinning electrode, cylindrical electrode as receiving electrode, electric field voltage was set to 15 kV for positive pressure and -1.5 kV for negative pressure, spinning temperature was set to 25 °C, ambient humidity was set to 30% RH, injection speed was set to 0.1 mm / min, aluminum foil was selected as receiving device, and the distance between spinning electrode and aluminum foil was 15 cm.

8. The method for preparing a composite nanofiber membrane for synergistically enhancing chemical warfare agent removal according to claim 6, characterized in that: The process of depositing PDA on PAN nanofiber membrane is as follows: The PAN fiber membrane was immersed in a Tris-HCl buffer solution, and dopamine hydrochloride self-polymerized and coated on the surface of the PAN fiber membrane.

9. The method for preparing a composite nanofiber membrane for synergistically enhancing chemical warfare agent removal according to claim 8, characterized in that: The pH of Tris-HCl buffer solution was 7.5, and the concentration of dopamine hydrochloride was 2 mg / mL.

10. Use of the composite nanofiber membrane for synergistically enhancing chemical warfare agent removal according to claim 1 for degrading chemical warfare agent simulants.

11. The use according to claim 10, characterized in that: The chemical warfare agent simulant is at least one of a nerve agent simulant and a corrosive agent simulant.

12. The use according to claim 11, characterized in that: The nerve agent simulant is DMNP, and the erosive agent simulant is CEES.

Citation Information

Patent Citations

  • Chemical warfare agent self-disinfection MOF (metal organic framework) fiber filtering membrane and preparation method thereof

    CN108310982A

  • Nano core-shell compound and composite fiber membrane for photothermal enhanced degradation of chemical warfare agent simulants and preparation methods and application of nano core-shell compound and composite fiber membrane

    CN109603910A

  • Titanium-iron MOF solid, process for obtaining it and use thereof for the degradation of compounds

    CA3165540A1

  • Thin film material for inhibiting lithium dendrite growth and preparation method thereof

    CN110592807A